WHO Indicators and its Compliance by General Practitioners of Lahore, Pakistan: WHO Indicators and its Compliance by General Practitioners of Lahore, Pakistan - Farooq, Muhammad Asim; Khan, Izzatullah; Haleem Khan, Daulat; Ahsan, Anam; Hussain, Atif; Mansoor, Irum; Parveen, Rashida (Iranian Journal of Pharmaceutical Sciences, 2019)
Prescribing pattern is also important factor to identify the problems related to prescribing and best tool to improve the quality of prescription and patient care. The aim of current study was to evaluate the quality of prescription and prescribing practices as per WHO drug core indicators in Lahore, Pakistan. A descriptive and cross- sectional study was carried out to access the prescribing pattern in Lahore, Pakistan. A sample of 300 prescriptions were collected from well –known Pharmacies and hospitals located in Lahore, Pakistan. A Structured data collection form was designed. The standard world health organization (WHO) drugs core prescribing indicators were used to determine the prescribing pattern of physicians. Data was analyzed using IBM SPSS V21.0. The name of patients was mentioned 93% of total prescriptions. While age and sex mentioned on prescriptions were 67% and 53% respectively. Only 22% prescriptions were containing patient weight description.32% of total prescriptions were mentioned prescriber address. 16% of total prescriptions were containing patient address. While 60% of total prescriptions were mentioned specliazation of prescribers. The total numbers of drugs prescribed on all encounter was 1122. The average number of drugs prescribed per encounter was 3.74(optimal value 1.6-1.8). The total number of drugs prescribed under generic name was 0% (optimal value 100%). Antibiotics were 42.5% of total drug prescribed (optimal value 20-26.8). Injections were 19.25% of prescriptions (optimal value less 10%). Prescription writing is a tough task. The results of current study show a poor compliance rate of legal requirement required for prescription writing. Most of prescribers were deviated from standard guidelines. There is dare need to improve the knowledge about prescription writing and prescribing practices. Continuous education is required to ensure the rational prescribing at Lahore, Pakistan in future.